Masalah Sosial Dalam Novel Kami (Bukan) Jongos Berdasi Karya J.S. Khairen - Annisa, Khairatul; Muhammad Ismail Nasution (Universitas Negeri Padang, 2024)
Social problems are problems that must be understood and studied. The aim of this research is to describe the form, causes and impacts of social problems in the novel Kami (Not) Jongos Berdasi by J.S.Khairen. The object of this research is the novel Kami (Not) Jongos Berdasi by J.S.Khairen, which was published in 2019. This research is literary research using descriptive methods. Words, phrases, clauses and sentences are data that show the form, causes and impacts of social problems in the novel Kami (Not) Jongos Berdasi by J.S.Khairen. The instrument for this research was the author himself with the help of a recording sheet. Data collection techniques include reading and understanding the novel, marking words, phrases, clauses and sentences, literature review and taking an inventory of the characters in the novel. Data triangulation technique is used as a validation technique. The data analysis technique is classifying and analyzing the data, then interpreting the data and concluding the data analysis. The results of the research state that (1) the forms of social problems in the novel are poverty, crime, family disorganization, adolescent problems, population problems and violence problems, (2) the causes of social problems in the novel are caused by economic factors, biological factors and biopsychological factors, ( 3) the impact of social problems in the novel in the form of increasing crime rates, social inequality, the emergence of deviant behavior, increasing unemployment and group divisions.